The Influence of Brand Equity and Price on Decisions Purchasing Delicious Noodles For Students in Padang City: The Influence of Brand Equity and Price on Decisions Purchasing Delicious Noodles For Students in Padang City - Paramita Ismaroiming; Jumiatul Mulya (International Journal of Management and Business (IJMB), 2024)
Abstract: This research aims to find out how much influence brand equity and price have on the decision to purchase Sedaap noodles among students in Padang City. The type of research used is quantitative research. The number of samples in this study was 96 people. The analytical method used is multiple linear regression analysis, using hypothesis testing, namely the t test and F test. The results of the research show that Brand Equity has a positive and significant effect on the Purchase Decision of Sedaap Noodles among Students in Padang City. Price has a positive and significant effect on the decision to purchase Sedaap noodles among students in the city of Padang. Based on the F Test, Brand Equity and Price simultaneously influence the Purchasing Decision of Sedaap Noodles among Students in Padang City. The R Square value is 97.7% which means that Brand Equity and Price are able to influence the Purchasing Decision of Sedaap Noodles among Padang City Students by 97.7%. The remaining 2.3% is influenced by other factors not examined in this research such as product quality, promotion.